Perspective of Life-Cycle Cost Analysis and Risk Assessment for Airport Pavement in Delaying Preventive Maintenance - Babashamsi, P. (MDPI, 2022)
Airport pavements deteriorate with age due to the impacts of environmental factors and air traffic. There is a dearth of studies on the scheduling of airport pavement maintenance and the importance of assessing the different scheduling strategies using Life-Cycle Cost Analysis (LCCA). An analysis of the costâbenefit study of a delay in maintenance alternatives should be done to determine whether a one-year delay is beneficial. This study concerns airport pavement management systems and the significance of a delay in several maintenance and preservation strategies depending on the analysis of inputs and outputs based on data from the Rocky Mountain Metropolitan airport in Jefferson County, United States. Herein, four preventive maintenance strategies were reviewed: three of the strategies involve crack treatment, namely crack sealing, patching, and a slurry seal, while the review of surface treatment only looks at the overlay method, which is done based on two Pavement Condition Indices (PCI 90 and PCI 80), and the resulting improvement in service life. The novel integrated LCCA + LCA program, namely PAVECO, is introduced in this research to compare alternatives from perspectives that are not purely economic, by considering direct costs, indirect costs, and salvage values. Results show that a one-year delay in preventive maintenance increases the deterministic life cycle cost by 16. Based on the sensitivity analysis of the discount rate, the total cost shows more than a 10 decrease as the discount rate increased by 1. Additionally, the uncertainty in PCI 80 is higher than that in PCI 90. The probabilistic model provides stakeholders with the opportunity to consider the alternative which is most suited to the allocated budget. It can be concluded that, based on the simulation of the effects of maintenance activities during the pavement life-cycle, preventive maintenance should start when the roads are in good condition to prompt managers and stakeholders to analyze the costs during the life-cycle. Postponing the preventive maintenance of airport pavement could raise the cost by 50. The maintenance of airport pavements in developing countries is still one of the main challenges of pavement management due to the maintenance only being done when it is necessary. Â© 2022 by the authors. Licensee MDPI, Basel, Switzerland.